The journal of microbiology, biotechnology and food sciences (Faculty of Biotechnology and Food Sciences, 2011)
"The Journal of Microbiology, Biotechnology and Food Sciences is an Open Access, peer-reviewed scientific journal for publishing of scientific articles from agriculture, animals and plants microbiology including bacteria, fungi, yeats, algae, protozoa and viruses. Microbial, animal and plants biotechnology and physiology, modern biotechnologies, genetics, molecular biology, agriculture and food chemistry, food control, evaluation and processing of food, food biochemistry and environmental science of agriculture."